IMPLEMENTASI KEBIJAKAN PEMELIHARAAN OBJEK PEMAJUAN KEBUDAYAAN DI KAMPUNG ADAT CIKONDANG KABUPATEN BANDUNG - Komara, M Indra; Santosa, Pandji (Ilmu Pemerintahan Universitas Langlangbuana, 2023)
The problem in this study is that the Implementation Of Cultural Advancement Object Maintenance Policy In Cikondang Traditional Village Bandung District, has not been optimized. The theoretical approach used in this research is Policy Implementation according to Van Meter and Van Horn in Agustino (2016: 133-136) which consists of six dimensions, namely: policy size and objectives, resources, characteristics of implementing agents, attitudes/tendencies (dispositions), interorganizational communication and coordination implementing activities, as well as the economic, social and political environment. Based on this theoretical approach, the researcher formulates a proposition: Implementation Of Cultural Advancement Object Maintenance Policy In Cikondang Traditional Village Bandung District will run optimally if it implements the dimensions of policy size and objectives, resources, characteristics of implementing agents, attitudes / tendencies (dispositions), inter-organizational communication and coordination implementing activities, as well as the economic, social and political environment. The research method used is descriptive research method, with a qualitative approach, while data is obtained through literature study, participant observation, in-depth interviews and documentation. The results showed that the Cultural Advancement Object Maintenance Policy in Cikondang Traditional Village in its implementation had obstacles. Efforts are made to overcome obstacles in the implementation of the Cultural Advancement Object Maintenance Policy in Cikondang Traditional Village by verifying the Cikondang Traditional Village area as one of the cultural heritage sites in Bandung District.